The application of building audit and energetic certificate to the property management - Życzyńska, Anna (Budownictwo i Architektura / Civil and Architectural Engineering, 2013)
The paper demonstrates the basic regulations in force concerning the preparation of audits and energetic certificates of buildings whose essential differences were subsequently pointed out. The relevance of the energetic audit performance and its use in gaining the financial support and managing the thermal modernisation investments was examined. Furthermore, the energetic standard currently in force for new and reconstructed buildings was discussed. The role and responsibilities of a property administrator within this scope were presented. Last but not least, the legal acts referring to the realisation of such a research were mentioned.